Conversations about History. - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About History, Volume 1, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading historians with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. David Cannadine, Professor of History, Princeton University;2. Michael Gordin, Rosengarten Professor of Modern and Contemporary History at Princeton University;3. Margar.